PENGARUH STATUS SOSIAL EKONOMI, MODERNITAS INDIVIDU, GAYA HIDUP TERHADAP PARTISIPASI PETANI DALAM PELESTARIAN NILAI BUDAYA PERTANIAN DI KABUPATEN TABANAN PROVINSI BALI - I Kade Sanjana Duaja (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2011)
The study investigated the effect of social economic status, individual modernity, life style towards farmer’s participation in continuation of cultural value. Data on strategy use is gathered through a questionnaire (n=250) and analyzed by using Path Analysis. Results show that there status and farmer’s participation. There is direct effect between individual modernity and farmer’s participation. There is not indirect effect between social economic status through life style and farmer’s participation. There is indirect effect between individual modernity and life style towards participation in continuants of culture value. Economic status, individual modernity and life style are determined factors of cultural value of community.